Ion Channels as Marine Drug Targets - Sabatier, Jean-Marc (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Marine Drugs is glad to announce its first Special Issue book on "ion channels" related research: Under the great stewardship of the Guest Editor, Dr. Jean-Marc Sabatier, four advanced research articles and three comprehensive review papers were collected in the Special Issue "Ion Channels as Marine Drug Targets". Join us to explore the advanced research outcomes in this field: α-Conotoxin RgIA and a potent analog, RgIA4, in treatment of pain; botulinum toxin-chitosan nanoparticles in treatment of atrial fibrillation; 27-amino acid (aa)-long δ-conotoxin TxVIA that modulates mammalian CaV3.x; first venomics study of Conus tulipa venom; review on marine toxins targeting Kv1 channels; review on synthetic approaches to zetekitoxin AB; and review on marine natural products and drug resistance in latent tuberculosis. The second edition of this Special Issue is open for submissions, we look forward to your contribution.